β(2)-Adrenoceptors increase translocation of GLUT4 via GPCR kinase sites in the receptor C-terminal tail - Dehvari, Nodi (Blackwell Publishing Ltd, 2012)
BACKGROUND AND PURPOSE: β-Adrenoceptor stimulation induces glucose uptake in several insulin-sensitive tissues by poorly understood mechanisms. EXPERIMENTAL APPROACH: We used a model system in CHO-K1 cells expressing the human β(2)-adrenoceptor and glucose transporter 4 (GLUT4) to investigate the signalling mechanisms involved. KEY RESULTS: In CHO-K1 cells, there was no response to β-adrenoceptor agonists. The introduction of β(2)-adrenoceptors and GLUT4 into these cells caused increased glucose uptake in response to β-adrenoceptor agonists. GLUT4 translocation occurred in response to insulin and β(2)-adrenoceptor stimulation, although the key insulin signalling intermediate PKB was not phosphorylated in response to β(2)-adrenoceptor stimulation. Truncation of the C-terminus of the β(2)-adrenoceptor at position 349 to remove known phosphorylation sites for GPCR kinases (GRKs) or at position 344 to remove an additional PKA site together with the GRK phosphorylation sites did not significantly affect cAMP accumulation but decreased β(2)-adrenoceptor-stimulated glucose uptake. Furthermore, inhibition of GRK by transfection of the βARKct construct inhibited β(2)-adrenoceptor-mediated glucose uptake and GLUT4 translocation, and overexpression of a kinase-dead GRK2 mutant (GRK2 K220R) also inhibited GLUT4 translocation. Introducing β(2)-adrenoceptors lacking phosphorylation sites for GRK or PKA demonstrated that the GRK sites, but not the PKA sites, were necessary for GLUT4 translocation. CONCLUSIONS AND IMPLICATIONS: Glucose uptake in response to activation of β(2)-adrenoceptors involves translocation of GLUT4 in this model system. The mechanism is dependent on the C-terminus of the β(2)-adrenoceptor, requires GRK phosphorylation sites, and involves a signalling pathway distinct from that stimulated by insulin.